Perancangan Website Pemesanan Menggunakan Metode Waterfall Pada Cafe Ungu Universitas Amikom Purwokerto - Nur Adiya, Az Zahra Dwi; Anggraeni, Dea Lili; Al Raidhan, Muhammad Akhmal; Tarwoto (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2025)
The advancement of information technology has significantly transformed operational management in various sectors, including the culinary industry. Cafe Ungu at Universitas Amikom Purwokerto serves as a campus facility offering a variety of food and beverages to students, staff, and visitors. However, the conventional ordering method relying on direct interaction often leads to long queues and recording errors, hindering service effectiveness. To address this issue, this study designs a web-based ordering information system using the Waterfall method, encompassing the stages of requirements analysis, design, development, testing, and maintenance. The system is designed to allow customers to place orders online, assist administrators in managing orders, and provide transaction data for business analysis purposes. The implementation results indicate that this system can improve operational efficiency, reduce ordering errors, and enhance customer satisfaction. Therefore, this information system is expected to be a strategic solution for Cafe Ungu in addressing order management challenges in the digital era.